2020
DOI: 10.1038/s41598-020-69677-6
|View full text |Cite
|
Sign up to set email alerts
|

Cutibacterium acnes regulates the epidermal barrier properties of HPV-KER human immortalized keratinocyte cultures

Abstract: our skin provides a physical barrier to separate the internal part of our body from the environment. Maintenance of complex barrier functions is achieved through anatomical structures in the skin, the stratified squamous epithelium specialized junctional organelles, called tight junctions (TJs). Several members of our microbial communities are known to affect the differentiation state and function of the colonized organ. Whether and how interactions between skin cells and cutaneous microbes, including Cutibact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…C. acnes is, directly and indirectly, involved in the pathogenesis of the common inflammatory skin disease—acne vulgaris. The free fatty acids and the pro-inflammatory virulence factors—porphyrins, produced by these bacteria, can cause skin inflammation [ 23 , 28 , 29 ].…”
Section: Interactions Between Skin Microorganismsmentioning
confidence: 99%
“…C. acnes is, directly and indirectly, involved in the pathogenesis of the common inflammatory skin disease—acne vulgaris. The free fatty acids and the pro-inflammatory virulence factors—porphyrins, produced by these bacteria, can cause skin inflammation [ 23 , 28 , 29 ].…”
Section: Interactions Between Skin Microorganismsmentioning
confidence: 99%
“…8a,b and Supplementary Table 4; Kruskal-Wallis test P < 0.05 and log 10 Linear Discriminant Analysis score (LDA) > 2.0). C. acnes is a ubiquitous commensal skin microbe, dominant in oily skin sites in younger adults 29 with key roles in immunomodulation, epithelial barrier maintenance and protecting the host from pathogens as well as acne vulgaris [49][50][51][52] . At oily sites, Streptococcus parasanguinis was significantly enriched in SNFD, whereas Propionibacterium namnetense was significantly θ = 1 represents 100% similarity in shared species and their relative abundance; θ = 0 indicates no (0%) similarity.…”
Section: Composition Of the Skin Gut And Oral Microbiome Of Older Adultsmentioning
confidence: 99%
“…Indeed, the data of Nograles et al 42 support this theory as IL‐17 and IFN‐γ treatment caused significant downregulation of FLG, KRTs, CLDN1, DSGs and DSCs in primary human keratinocytes. In addition, Bruewer et al 43 demonstrated that the pro‐inflammatory cytokines IFN‐γ and TNF‐α can disrupt the properties of the epithelial barrier, while a recent study conducted by Bolla et al 44 suggests that Cutibacterium acnes might impact the skin barrier properties by activating innate immune responses and inducing inflammation. However, on the other hand, sebum lipids are also potential candidates as reflected in the term sebaceous immunobiology 45,46 .…”
Section: Discussionmentioning
confidence: 99%